Leonard Cohen's Traffic in Alterity in Beautiful Losers - Lesk, Andrew (Studies in Canadian Literature, 1997)
While Beautiful Losers deserves its reputation as a subversive text insomuch as its overall libidinal freedom -- the "obscene" references to the anal and scatological in particular -- can be seen as disrupting sexual norms, in the end Cohen's example of what Linda Hutcheon tags "postmodern metafiction" simply reinscribes and reaffirms the (hetero)normative order of dominant knowledges, social hierarchies, and binary oppositions. An analysis of Beautiful Losers drawing on the criticism of Irigaray, Sedgwick, and Seidman suggests that despite postmodern claims for Cohen's disruption of traditional constructions and understandings of gendered identities in his narrative, the novel is still governed by a rhetoric of hierarchical dominant male discourses. The traffic in alterity presented in Cohen's text is falsely congruent with the presumption that simple evocation of otherness implies understanding and knowledge of the Other's specific and discrete difference.